Comparison of the Predictive Value of Myelography, Computed Tomography and MRI on the Treadmill Test in Lumbar Spinal Stenosis - Moon, Eun-Su (Yonsei University College of Medicine, 2005)
To date, there have been no prospective, objective studies comparing the accuracy of the MRI, myelo-CT and myelography. The purpose of this study is to compare the diagnostic and predictive values of MRIs, myelo-CTs, and myelographies. Myelographies with dynamic motion views, myelo-CTs, MRIs and exercise treadmill tests were performed in 35 cases. The narrowest AP diameter of the dural sac was measured by myelography. At the pathologic level, dural cross-sectional area (D-CSA) was calculated in the MRI and Myelo-CT. The time to the first symptoms (TAF) and the total ambulation time (TAT) were measured during the exercise treadmill test and used as the standard in the comparison of correlation between radiographic parameters and walking capacity. The mean D-CSA by CT was 58.3 mm(2) and 47.6 mm(2) by MRI. All radiographic parameters such as AP diameters and D-CSA have no correlation to TAF or TAT (p>0.05). Our data showed no statistically significant differences in the correlation of the patients' walking capacity to the severity of stenosis as assessed by myelography, myelo-CT and MRI.